Annual Assessment of Transport Noise Using Representative Time Measurements. (2016) - Jagniatinskis, Aleksandras; Fiks, Boris; Zaporozhets, Oleksandr
Abstract: By the World Health Organization (WHO) data reported in Burden of disease from environmental noise "one in three individuals is annoyed during the daytime and one in five has disturbed sleep at night because of traffic noise". By these data the odds of incidence of disease rise to about 10% when LAeq, day noise level increase from 55–60 dB to 65–70 dB. The main descriptor for evaluation of the environmental noise impact in the leaving areas by EU Directives is composite annual day-evening-night level Lden and sometimes annual Lnight level is used. These descriptors are mandatory used in noise mapping, mainly calculated with appropriate methods. The problems arise in cases, when these annual values must be evaluated from short time measurements. The replacement of full year measurement by choosing a shorter time interval is suggested in this work using the conception of representative time interval. The time interval is understood as a representative when selected sampling interval contains an appropriate amount of transportation noise events (passing bys or flying bys) and that allows to estimate annual noise descriptors with required accuracy. In paper the particularities for representative sample definition for cases of road, aircraft and rail transport are analyzed. It is shown, that statistical distribution of measured sound exposure levels of transportation noise events may serve as a basis for representative sample determination and may be used for annual noise assessment of aircraft flying bys, rail transport passing bys and road vehicle passing bys in suburban type of roads. As an example in Lithuanian traffic conditions it is shown, that the usage of consecutive seven days (one week) measurements under normal weather conditions is applicable as a representative time interval for annual urban traffic noise assessment.